PENGEMBANGAN KURIKULUM PARADIGMA BARU MELALUI PENGUATAN BERFIKIR KRITIS PADA SISWA SD DI KELAS TINGGI - Komang Surya Adnyana; Ni Putu Kusuma Widiastuti; I Wayan Suastra (Jurnal Pendidikan Dasar Flobamorata, 2022)
Problem solving skills, creative thinking and critical thinking have become the center of attention of educators, researchers, entrepreneurs, and the mass media for several years. This can be seen from the fact that critical thinking skills will determine a person's endurance/competitiveness in recognizing to be the best because it will increase the competitive power of the individual, according to the opinion that critical thinking skills have been recognized as important skills for successful learning, and working in the 21st century (A person who has critical skills and good communication skills will adapt well to changes in the academic context and the world of work. Critical thinking is an important ability for students, so critical thinking becomes one of the activities that must be developed and taught in the world of work). every subject, because the ability to think is not innate and does not develop naturally. The method in this study uses the literature review method by examining curriculum development through critical thinking learning